2016
DOI: 10.1590/0004-282x20150217
|View full text |Cite
|
Sign up to set email alerts
|

Increased sexual arousal in patients with movement disorders

Abstract: Increased of sexual arousal (ISA) has been described in different neurological diseases. The purpose of this study was present a case series of ISA in patients with movement disorders. Method Fifteen patients with different forms of movement disorders (Parkinson’s disease, Huntington’s disease, Tourette´s syndrome, spinocerebellar ataxia type 3), were evaluated in the Movement Disorders Unit of the Federal University of Paraná. Results Among Parkinson’s disease patients there were seven cases with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In 1 prospective study, 2 PD patients (both male) were identified to have HSD following bilateral STN-DBS. 76 However, it is well recognized that HSD is also observed in PD patients who have not undergone DBS surgery as a consequence of dopaminergic agonist medication and levodopa abuse. In this particular study, the adjustment of DBS parameters resulted in an improvement in HSD symptoms in at least 1 of the patients; however, it is not clear if this also coincided with medication reduction 76 (Table 5).…”
Section: Sexual Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1 prospective study, 2 PD patients (both male) were identified to have HSD following bilateral STN-DBS. 76 However, it is well recognized that HSD is also observed in PD patients who have not undergone DBS surgery as a consequence of dopaminergic agonist medication and levodopa abuse. In this particular study, the adjustment of DBS parameters resulted in an improvement in HSD symptoms in at least 1 of the patients; however, it is not clear if this also coincided with medication reduction 76 (Table 5).…”
Section: Sexual Domainmentioning
confidence: 99%
“…Most notably increased sexual arousal and hypersexual disorder (HSD). In 1 prospective study, 2 PD patients (both male) were identified to have HSD following bilateral STN‐DBS . However, it is well recognized that HSD is also observed in PD patients who have not undergone DBS surgery as a consequence of dopaminergic agonist medication and levodopa abuse.…”
Section: Sexual Domainmentioning
confidence: 99%
“…In contrast, a significantly higher frequency of sexual dysfunction was observed in Rukmini et al's study 45 . Also, in another investigation, hypersexual disorder (HSD) was reported as a negative outcome of STN‐DBS observed in two patients 53 . Nevertheless, this can be attributed to the misuse of levodopa and dopaminergic agonist drugs.…”
Section: Discussionmentioning
confidence: 96%
“…45 Also, in another investigation, hypersexual disorder (HSD) was reported as a negative outcome of STN-DBS observed in two patients. 53 Nevertheless, this can be attributed to the misuse of levodopa and dopaminergic agonist drugs.…”
Section: Sexual Problemsmentioning
confidence: 99%